Welding paste and preparation method thereof

By using a combined welding slurry of micro-indium powder, micro-thermal conductive powder and nano-metal elemental powder, the problem of insufficient thermal conductivity and plasticity of existing welding materials in high temperature environments is solved, and the welding effect of high thermal conductivity and plasticity is achieved. In the fields of IGBT packaging and other fields.

CN116140867BActive Publication Date: 2025-02-25KUNSHAN BAIROU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211721879.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-02-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Existing welding materials are difficult to meet thermal conductivity and plasticity in high-temperature environments while improving, especially in the field of IGBT packaging.

Method used

Using a combination of micro-indium powder, micro-thermal conductive powder and nano-metal elemental powder, a welding slurry with high thermal conductivity and plasticity can be achieved through the joint action of the powder, which can be sintered at low temperature at 200°C.

Benefits of technology

The thermal conductivity of the welding slurry is greater than 80W/m·K, and has excellent plasticity. It is suitable for large-area bonding, such as IGBT packaging fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116140867B_ABST
    Figure CN116140867B_ABST
Patent Text Reader

Abstract

The present application relates to the field of thermal conductive paste technology, and in particular to a welding paste and a preparation method thereof. The welding paste includes the following weight components: 1-90 parts of micron indium powder; 0-90 parts of micron thermal conductive powder, and the thermal conductivity of the micron thermal conductive powder is ≥200W / mK; 1-90 parts of nano metal powder; 2-5 parts of organic solvent; 0.5-1 parts of activator; 0.2-1 parts of neutralizer; 0.1-1 parts of thickener. The welding paste of the present application contains three powder materials of micron indium powder, micron thermal conductive powder and nano metal powder in specific weight portions. Based on the joint action of the powder, low-temperature sintering at 200°C can be achieved, and the thermal conductivity of the solidified material after sintering can be greater than 80W / m·K, which has the characteristics of excellent plasticity and thermal conductivity, and has a wide range of applications, especially suitable for large-area bonding with high thermal conductivity requirements such as IGBT packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of thermal conductive pastes, and in particular, relates to a welding paste and a preparation method thereof. Background Art

[0002] With the rapid development of consumer electronics, security, industrial control, automotive electronics, new energy and many other fields, the demand for power converter capacity for energy conversion and storage is increasing. As a result, how to quickly dissipate the large amount of heat generated during the energy conversion process has become a serious problem. Therefore, interface interconnect materials with high thermal conductivity and low interface thermal resistance have become an urgent need in the electronic packaging industry.

[0003] For example, patent CN106910691A discloses a heat dissipation structure and packaging process of an insulated gate bipolar transistor (IGBT) module in a power converter, which applies graphene material in the form of a heat dissipation film to the surface of an IGBT chip with a high heat flux density, and applies it between the chip and the substrate, the heat sink and the substrate in the form of a filling enhanced conductive and thermally conductive adhesive, and solves the heat dissipation problem of the IGBT module in the power converter through the interconnection method of chip mounting. This solution has a complex process, and the packaging material uses organic components, and there is a problem of resin aging failure in a high temperature environment. Patent CN106373954A discloses a sintered IGBT module using nano silver solder paste, including two circular plate-shaped metal electrodes consisting of an emitter and a collector, a cylindrical ceramic tube shell, an IGBT boss on the emitter plate shell, a freewheeling diode boss, and an IGBT single-chip welding sub-module mounted on the IGBT boss and a freewheeling diode single-chip welding sub-module on the freewheeling diode boss, respectively. In the single-chip welding sub-module, the lower molybdenum substrate and the IGBT and freewheeling diode are connected by low-temperature sintering using nano silver solder paste as the thermal interface material. The patent adopts a hot pressing process to form welding, and pressurization will cause mechanical damage to the IGBT chip, and it is also brittle and prone to holes. In the later high-temperature service process, it is easy to produce cracks due to thermal stress, forming a greater thermal resistance.

[0004] Therefore, in power devices represented by IGBT, because the components are complex and possibly heterogeneous, the thermal process deformation is large, which places higher requirements on the plasticity of the connection paste, and the above-mentioned connection materials cannot meet the plastic deformation requirements. Moreover, in the field of high thermal conductivity, general low-temperature welding thermal conductive materials are difficult to meet the thermal conductivity requirements of more than 70W / m·K. Tin-containing welding solutions are prone to failure in high-temperature environments due to their high-temperature melting characteristics, and solder solutions are difficult to meet higher application scenarios with thermal conductivity requirements greater than 70W / m·K. The nano-silver copper sintering solution is prone to stress release and cracks when facing large-area welding or thermal expansion coefficient (CTE) mismatch. Summary of the invention

[0005] The purpose of the present application is to provide a solder paste and a preparation method thereof, aiming to solve the problem of how to provide a solder paste having both good plasticity and thermal conductivity.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a welding slurry, comprising the following components by weight:

[0008] 1-90 parts of micron indium powder;

[0009] 0-90 parts of micron thermal conductive powder, and the thermal conductivity of the micron thermal conductive powder is ≥200W / mK;

[0010] 1-90 parts of nano metal powder;

[0011] 2-5 parts of organic solvent;

[0012] Activator 0.5-1 part;

[0013] Neutralizer 0.2-1 part;

[0014] Thickener 0.1-1 part.

[0015] In one embodiment,

[0016] 30-80 parts of micron indium powder;

[0017] 10-40 parts of micron thermal conductive powder;

[0018] 5-30 parts of nano metal powder.

[0019] In one embodiment, the particle size of the micron indium powder is 0.1 μm to 10 μm, the particle size of the micron thermal conductive powder is 0.1 μm to 10 μm, and the particle size of the nano metal powder is 20 nm to 100 nm.

[0020] In one embodiment, the micron thermal conductive powder is selected from at least one of micron aluminum powder, micron silver powder, micron copper powder, micron silver-copper alloy powder, micron diamond powder and micron silver-coated diamond powder.

[0021] In one embodiment, the nano-metal powder is selected from at least one of nano-silver powder and nano-copper powder.

[0022] In one embodiment, the organic solvent is selected from at least one of ethylene glycol butyl ether, propylene glycol methyl ether, diethylene glycol butyl ether and propylene glycol ethyl ether.

[0023] In one embodiment, the activator is selected from at least one of n-caproic acid, glutaric acid, adipic acid and citric acid; and / or

[0024] The neutralizing agent is selected from at least one of triethanolamine, triisopropanolamine, tetramethylpropylenediamine and N,N-dimethylethanolamine; and / or

[0025] The thickener is selected from at least one of polyethylene glycol, polyvinyl butyral and polyvinyl pyrrolidone.

[0026] In a second aspect, the present application provides a method for preparing a welding slurry, comprising the following steps:

[0027] Providing various raw material components in the welding paste;

[0028] Micron indium powder, micron thermal conductive powder, nano metal element powder, organic solvent, activator, neutralizer and thickener are mixed to obtain welding slurry.

[0029] In one embodiment, the step of mixing micron indium powder, micron thermal conductive powder, nano metal powder, organic solvent, activator, neutralizer and thickener includes: first mixing, stirring and heating the organic solvent, activator, neutralizer and thickener to obtain a mixed solution; then dispersing the micron indium powder, micron thermal conductive powder and nano metal powder in the mixed solution.

[0030] In one embodiment, the dispersing comprises ultrasonic dispersing.

[0031] The welding slurry provided in the first aspect of the present application contains three powder materials, namely, micron indium powder, micron thermal conductive powder and nano metal element powder, in specific weight proportions; among them, the high plasticity metal property based on the micron indium powder can effectively release the stress formed by large-area bonding, thereby overcoming the crack defects of the welding slurry caused by stress concentration, and the addition of micron thermal conductive powder with a thermal conductivity coefficient ≥ 200W / mK can improve the thermal conductivity of the welding slurry, and suitable nano metal element powder can be combined with micron-level powder to form a metal composite with good comprehensive performance, further improving the comprehensive performance of the slurry; in summary, the welding slurry provided in the present application can achieve low-temperature sintering at 200°C through the joint action of powders, and the thermal conductivity of the solidified material after sintering can be greater than 80W / m·K, and it has the characteristics of excellent plasticity and thermal conductivity, and has a wide range of applications, and is particularly suitable for use in large-area bonding with high thermal conductivity requirements such as IGBT packaging.

[0032] The second aspect of the present application provides a method for preparing a solder paste, which is obtained by mixing a certain weight portion of micron indium powder, micron thermal conductive powder, nano metal powder, organic solvent, activator, neutralizer and thickener. The preparation method is not only simple in process and easy to operate, but also based on the formula raw materials containing specific weight portions of micron indium powder, micron thermal conductive powder and nano metal powder, through the joint action of the three powders, the solder paste material prepared by the present application can release stress through plastic deformation, thereby having the characteristics of excellent plasticity and thermal conductivity, and can be suitable for use in large-area bonding with high thermal conductivity requirements such as IGBT packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a SEM image of nano silver powder in the solder paste provided in Example 1 of the present application;

[0035] Figure 2 is a distribution diagram of solidified elements in the welding paste provided in Example 1 of the present application;

[0036] Figure 3 The copper-copper interconnected sandwich structure is obtained after using the solder paste provided in Example 1 of the present application;

[0037] Figure 4 This is a diagram of the interface between copper and solidified material after using the solder paste provided in Example 1 of the present application. DETAILED DESCRIPTION

[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0039] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0040] In the present application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.

[0041] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0043] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0044] It should be noted that the micron-level size referred to in this application includes the submicron-level of 100nm to 1μm and the micron-level of 1μm to 100μm; and the nanometer-level size refers to the size of 0.1nm to 100nm.

[0045] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0046] In a first aspect, an embodiment of the present application provides a welding paste, comprising the following components by weight:

[0047] 1-90 parts of micron indium powder;

[0048] 0-90 parts of micron thermal conductive powder, and the thermal conductivity of the micron thermal conductive powder is ≥200W / mK;

[0049] 1-90 parts of nano metal powder;

[0050] 2-5 parts of organic solvent;

[0051] Activator 0.5-1 part;

[0052] Neutralizer 0.2-1 part;

[0053] Thickener 0.1-1 part.

[0054] The welding slurry provided in the embodiment of the present application contains three powder materials of micron indium powder, micron thermal conductive powder and nano metal element powder in specific weight proportions; among them, the high plasticity metal property based on the micron indium powder can effectively release the stress formed by large-area bonding, thereby overcoming the crack defects of the welding slurry caused by stress concentration, and the addition of micron thermal conductive powder with a thermal conductivity coefficient ≥ 200W / mK can improve the thermal conductivity of the welding slurry, and suitable nano metal element powder can be combined with micron-level powder to form a metal composite with good comprehensive performance, further improving the comprehensive performance of the slurry; in summary, the welding slurry provided in the present application can achieve low-temperature sintering at 200°C through the joint action of powders, and the thermal conductivity of the solidified material after sintering can be greater than 80W / m·K, and it has the characteristics of excellent plasticity and thermal conductivity, and has a wide range of applications, and is particularly suitable for use in large-area bonding with high thermal conductivity requirements such as IGBT packaging.

[0055] In one embodiment, the micron indium powder can be a submicron powder of 0.1 μm to 1 μm or a micron powder of 1 μm to 100 μm. The thermal conductivity of indium powder is about 82 W / mK at 25°C, so the thermal conductivity is greater than 80 W / mK, and the Mohs hardness is 1.2. It is a key component that provides thermal conductivity and plastic deformation of the welding slurry. The high plasticity metal property of micron indium powder can effectively release the stress formed by large-area bonding and overcome the crack defects caused by stress concentration in the welding slurry. Further, the average particle size of micron indium powder can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc. The weight of micron indium powder can be 1-90 parts, such as 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, etc.

[0056] In one embodiment, the micron thermal conductive powder is a high thermal conductivity micron metal powder with a thermal conductivity of ≥200W / mK, which can be a submicron powder of 0.1μm to 1μm or a micron powder of 1μm to 100μm, mainly used as the skeleton part of the thermal conductive network structure; specifically, the above-mentioned high thermal conductivity micron thermal conductive powder is selected from at least one of micron aluminum powder, micron silver powder, micron copper powder, micron silver-copper alloy powder, micron diamond powder and micron silver-plated diamond powder. The addition of micron thermal conductive powder with a thermal conductivity greater than 200W / mK can improve the thermal conductivity of the welding slurry. Further, the average particle size of the micron thermal conductive powder can be 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, etc. The weight proportion of the micron thermal conductive powder can be 0-90 parts, such as 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, etc.

[0057] In one embodiment, nano-metal powder can be sintered at 200-300°C or less, and can be the main functional phase for low-temperature welding of copper-copper interface, and is preferably at least one of nano-silver powder and nano-copper powder. Nano-metal powder is compounded with micron-sized powder to form a metal composite with good comprehensive performance, further improving the comprehensive performance of welding slurry. Further, the average particle size of nano-metal powder can be 0.1nm, 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 40nm, 50nm, 80nm, 90nm, 100nm, etc. The weight of nano-metal powder can be 1-90 parts, such as 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, etc.

[0058] In one embodiment, the organic solvent is an ether solvent, specifically, a mixture of at least one or more selected from ethylene glycol butyl ether, propylene glycol methyl ether, diethylene glycol butyl ether and propylene glycol ethyl ether, and the weight portion of the organic solvent can be 2-5 parts, such as 2 parts, 3 parts, 4 parts, 5 parts, etc. The activator is selected from at least one or more of n-hexanoic acid, glutaric acid, adipic acid and citric acid, and the weight portion of the activator can be 0.5-1 part, such as 0.5 part, 0.6 part, 0.8 part, 1 part, etc. The neutralizer is selected from at least one or more selected from triethanolamine, triisopropanolamine, tetramethylpropylenediamine and N,N-dimethylethanolamine, and the weight portion of the neutralizer can be 0.2-1 part, such as 0.2 part, 0.4 part, 0.8 part, 1 part, etc. The thickener is selected from at least one or more of polyethylene glycol, polyvinyl butyral and polyvinyl pyrrolidone, and the weight portion of the thickener can be 0.1-1 part, such as 0.2 part, 0.4 part, 0.8 part, 1 part, etc. Further, 0-1 part of organic corrosion inhibitors, such as phosphine carboxylic acid, mercaptobenzothiazole, benzotriazole and other heterocyclic compounds containing nitrogen oxides, can be included, specifically 0.2 part, 0.4 part, 0.8 part, 1 part, etc.

[0059] In a preferred embodiment, the solder paste includes the following weight components: 30-80 parts of micron indium powder, 10-40 parts of micron thermal conductive powder with a thermal conductivity of ≥200W / mK, 5-30 parts of nano metal powder, 2-5 parts of organic solvent, 0.5-1 part of activator, 0.2-1 part of neutralizer and 0.1-1 part of thickener; wherein the particle size of micron indium powder is 0.1μm to 10μm, the particle size of micron thermal conductive powder is 0.1μm to 10μm, and the particle size of nano metal powder is 20nm to 100nm. The solder paste formed by the combination of the above-mentioned particle sizes and weight parts of powders has better comprehensive effects of plasticity and thermal conductivity.

[0060] A second aspect of an embodiment of the present application provides a method for preparing a welding slurry, comprising the following steps:

[0061] S01: providing various raw material components in welding slurry;

[0062] S02: Mixing micron indium powder, micron thermal conductive powder, nano metal powder, organic solvent, activator, neutralizer and thickener to obtain welding slurry.

[0063] The preparation method of the solder paste provided in the embodiment of the present application is obtained by mixing a certain weight portion of micron indium powder, micron thermal conductive powder, nano metal powder, organic solvent, activator, neutralizer and thickener. The preparation method is not only simple in process and easy to operate, but also based on the formula raw materials containing specific weight portions of micron indium powder, micron thermal conductive powder and nano metal powder, through the joint action of the three powders, the solder paste material prepared in the present application can release stress through plastic deformation, thereby having the characteristics of excellent plasticity and thermal conductivity, and can be suitable for use in large-area bonding with high thermal conductivity requirements such as IGBT packaging.

[0064] In step S01: the raw material components in the welding slurry have been described in detail above and will not be repeated here.

[0065] Step S02 is a step of mixing the raw materials.

[0066] In one embodiment, the step of mixing micron indium powder, micron thermal conductive powder, nano metal powder, organic solvent, activator, neutralizer and thickener comprises: firstly mixing, stirring and heating the organic solvent, activator, neutralizer and thickener to obtain a mixed solution; then dispersing the micron indium powder, micron thermal conductive powder and nano metal powder in the mixed solution. In this way, the three powders of micron indium powder, micron thermal conductive powder and nano metal powder can be better dispersed in the welding slurry to obtain a uniformly dispersed welding slurry. Furthermore, the above dispersion includes ultrasonic dispersion.

[0067] In one embodiment, the preparation method of the welding slurry includes: step A, mixing an organic solvent, an activator, a neutralizer, a thickener and an organic corrosion inhibitor, and heating them until they are completely dissolved to form a mixed solution; step B, putting the mixed solution into a planetary mixer in proportion with nano metal element powder, micron indium powder, and micron thermal conductive powder, stirring them evenly, and dispersing them through a three-roll grinder, and ultrasonically dispersing them to form a uniformly dispersed welding slurry for copper-copper interface.

[0068] The above-mentioned low-temperature soldering slurry for copper-copper interface provided in the present application, its soldering slurry composition contains three powder functional bodies and a carrier, which can meet the requirements of sintering within 200°C, and the thermal conductivity of the solidified material after sintering is greater than 70W / m·K. During specific use, the soldering slurry is printed onto the polished copper surface through a steel screen and pre-cured at about 90 to 100°C. The pre-cured copper sheet slurry is placed face to face in a laminator, the pressure is maintained at 2 to 3MPa and the temperature is gradually increased to 180 to 200°C, and the temperature is maintained and the pressure is maintained for 1 to 2 hours. Such soldering slurry is particularly suitable for use in large-area (greater than 5mm×5mm) bonding with high thermal conductivity requirements, such as in the field of IGBT packaging.

[0069] The following describes the invention in conjunction with specific embodiments.

[0070] Example 1

[0071] A solder paste comprising the following components by mass percentage:

[0072]

[0073] The preparation method of the above-mentioned welding slurry comprises the following steps:

[0074] A. Evenly mix propylene glycol ethyl ether, glutaric acid, triisopropanolamine, benzotriazole and polyvinyl butyral, and heat until completely dissolved to prepare a mixture a;

[0075] B. Mixing mixture a with nano silver powder having an average particle size of 64 nm, and performing ultrasonic dispersion to obtain mixture b;

[0076] C. Mixture b and micron indium powder with an average particle size of 10 μm are placed in a planetary mixer and stirred evenly to form a welding slurry product that can eventually be used for copper-copper interface.

[0077] The use steps of the above solder paste include: printing the solder paste onto the polished copper surface through a steel screen, and pre-curing at about 100° C. Putting the pre-cured copper sheet paste face to face into a laminator, maintaining a pressure of 3MPa and gradually raising the temperature to 200° C., and baking for 1 hour.

[0078] Example 2

[0079] A solder paste comprising the following components by mass percentage:

[0080]

[0081] The preparation method of the above-mentioned welding slurry comprises the following steps:

[0082] A. Evenly mix butyl diethylene glycol, glutaric acid, triisopropanolamine, benzotriazole and polyethylene glycol, and heat until completely dissolved to prepare a mixture a;

[0083] B. Put half of the mixture a, micron copper powder with an average particle size of 10 μm, and micron indium powder with an average particle size of 10 μm into a planetary mixer and stir them evenly to obtain a mixture b;

[0084] C. Mixing the remaining half of the mixture a with nano silver powder having an average particle size of 50 nm, and performing ultrasonic dispersion to form a uniformly dispersed mixture c;

[0085] D. Put mixture b and mixture c into a planetary mixer and mix them evenly to form a welding slurry product.

[0086] The steps of using the above-mentioned solder paste include: printing the solder paste onto the polished copper surface through a steel screen, pre-curing at about 100°C, placing the pre-cured copper sheets face-to-face in a laminator, maintaining a pressure of 3MPa and gradually raising the temperature to 200°C, and baking at this temperature and pressure for 1h.

[0087] Example 3

[0088] A solder paste comprising the following components by mass percentage:

[0089]

[0090]

[0091] The preparation method of the above-mentioned welding slurry is the same as that of Example 2.

[0092] Example 4

[0093] A solder paste comprising the following components by mass percentage:

[0094] The preparation method of the above-mentioned welding slurry is the same as that of Example 2.

[0095] Example 5

[0096] A solder paste comprising the following components by mass percentage:

[0097]

[0098]

[0099] The preparation method of the above-mentioned welding slurry is the same as that of Example 2.

[0100] Example 6

[0101] A solder paste comprising the following components by mass percentage:

[0102]

[0103] The preparation method of the above-mentioned welding slurry is the same as that of Example 2.

[0104] Comparative Example 1

[0105] The micron indium powder in Example 1 was replaced with micron copper powder, and the rest were the same.

[0106] Comparative Example 2

[0107] The micron indium powder in Example 1 was replaced with micron silver powder, and the other contents were the same.

[0108] Performance Testing

[0109] The solder pastes of Examples 1 to 5 and Comparative Examples 1 to 2 were characterized, and the performance characteristics included:

[0110] (1) Welding strength test process: Take the welded copper sheet and cut it into 2mm*2mm cubes at 5 locations by wire cutting. Then fix it on the copper substrate with 305 solder paste. Use a thrust gauge to push the top copper sheet to test the thrust strength.

[0111] (2) Thermal conductivity test: The slurry was made into a solidified block at 200°C and 3 MPa pressure, and cut into modules with a diameter of 12.7 mm and a thickness of 2 mm by wire cutting. The thermal conductivity was tested by laser flash method.

[0112] (3) Remelting property test: The slurry is made into a solidified block at 200°C and 3 MPa pressure. A small amount of the solidified material is tested by DSC scanning repeatedly 10 times to check the remelting property of the slurry.

[0113] (4) Bending stress test: The copper sheet welded with slurry is bent 90 degrees with a curvature equal to 3 mm to observe whether there is cracking or peeling.

[0114] The corresponding evaluation items and standards are shown in Table 1, and the test results are shown in Table 2.

[0115] Table 1

[0116]

[0117] Table 2

[0118]

[0119] As can be seen from Table 2, the addition of micron indium powder can effectively improve the cracking caused by bending stress, and the thermal conductivity of the welding slurry is also greater than 100W / mk. Although the welding strength is smaller than that of the control ratio, it is greater than 10MPa. There is no remelting in the DSC test curve, so it can meet the application requirements of large-area bonding and high thermal conductivity.

[0120] In addition, taking the solder paste of Example 1 as an example, the SEM image of the nano silver powder is as follows: Figure 1 As shown in Figure 2, the distribution of solidified elements in the welding paste is as follows: Figure 2 After the solder paste is finally used, the copper-copper interconnect sandwich structure is as shown. Figure 3 As shown, the interface between copper and solidified material is as Figure 4 As shown. It can be seen that the solder paste of Example 1 of the present application has a good bonding effect when used for the copper-copper interface.

[0121] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A welding paste, characterized in that: The components include the following mass percentages: Micron indium powder 51.4%; Micron thermally conductive powder 20%, and the thermal conductivity of the micron thermally conductive powder is ≥ 200W / mK; Nano metal powder 23%; Organic solvent 4%; Activator 0.5%; Neutralizer 0.3%; Thickener 0.5%; Organic corrosion inhibitor 0.3%; The particle size of the micron indium powder is 10 μm; The micron thermally conductive powder is selected from micron silver-plated diamond powder, and the particle size of the micron thermally conductive powder is 10 μm; The nano-metal powder is selected from nano-silver powder, and the particle size of the nano-metal powder is 50 nm; The organic solvent is selected from diethylene glycol butyl ether; The activator is selected from glutaric acid; The neutralizing agent is selected from triisopropanolamine; The thickener is selected from polyethylene glycol; The organic corrosion inhibitor is selected from benzotriazole; The solder paste is used for IGBT packaging at a copper-copper interface.

2. A method for preparing a welding slurry, characterized in that: The following steps are involved: Providing the raw material components of the welding paste according to claim 1; The micron indium powder, the micron thermal conductive powder, the nano metal element powder, the organic solvent, the activator, the neutralizer, the organic corrosion inhibitor and the thickener are mixed to obtain the welding slurry.

3. The preparation method according to claim 2, characterized in that: The step of mixing the micron indium powder, the micron thermal conductive powder, the nano metal powder, the organic solvent, the activator, the neutralizer, the organic corrosion inhibitor and the thickener comprises: firstly mixing, stirring and heating the organic solvent, the activator, the neutralizer, the organic corrosion inhibitor and the thickener to obtain a mixed solution; and then dispersing the micron indium powder, the micron thermal conductive powder and the nano metal powder in the mixed solution.

4. The preparation method according to claim 3, characterized in that: The dispersion includes ultrasonic dispersion.

Citation Information

Patent Citations

  • Sintered IGBT (Insulated Gate Bipolar Transistor) module applying nanometer silver soldering paste and fabrication method of sintered IGBT module

    CN106373954A

  • Heat radiation structure of IGBT module in power converter and packaging process

    CN106910691A

  • Nano-composite low-temperature slurry as well as preparation method and application thereof

    CN114974656A